2018
DOI: 10.3390/ijerph15040773
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coworkers’ Safety Violations on an Individual Worker: A Social Contagion Effect within the Construction Crew

Abstract: This research developed and tested a model of the social contagion effect of coworkers’ safety violations on individual workers within construction crews. Both situational and routine safety violations were considered in this model. Empirical data were collected from 345 construction workers in China using a detailed questionnaire. The results showed that both types of safety violations made by coworkers were significantly related to individuals’ perceived social support and production pressure. Individuals’ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 84 publications
5
63
0
Order By: Relevance
“…On the one hand, coworkers could remind their peers not to perform an unsafe act so that workers behave safely [41]. On the other hand, coworkers' violations of safety rules or standards may be imitated by their peers, which has a dramatically adverse impact on individual safety behavior [42]. Managers have influences on workers in various ways.…”
Section: Social Group and Social Organizational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, coworkers could remind their peers not to perform an unsafe act so that workers behave safely [41]. On the other hand, coworkers' violations of safety rules or standards may be imitated by their peers, which has a dramatically adverse impact on individual safety behavior [42]. Managers have influences on workers in various ways.…”
Section: Social Group and Social Organizational Factorsmentioning
confidence: 99%
“…Ji et al [63] adopted the ABM method to simulate the scene of reinforcing steel bars on the construction site, and proposed the support of the workers can reduce the occurrence of the nonfatal incidents. Liang et al [42] developed a hybrid simulation approach that integrated System Dynamics (SD) and ABM to study the social contagion effect of safety violations within a construction crew. These studies have made great contributions to the field of construction safety simulation [49].…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…According to social cognition theory, individual workers always try to belong to a social group and adjust their own behaviours to what they believe is the socially acceptable within the crew (Roettger et al, 2017). When perceiving a positive group norm for safety behaviours (e.g., coworkers helps others' to achieve safety equipment when it is not available onsite), individuals will follow safety rules similarly to fit themselves with their groups (Liang, et al, 2018a(Liang, et al, , 2018b, and vice versa. Previous studies have confirmed that supervisors are critical for the formation of safety-related group norm within the construction crew.…”
Section: Group Safety Normmentioning
confidence: 99%
“…Traditional research regarding the TPB often included a univalent safety attitude which was predominantly divided into either positive or negative attitude. However, this univalent safety attitude is not consistent with the psychological conflicts when an individual violates safety rules on-site (Liang, Lin, Zhang, & Su, 2018a). It's a universal phenomenon on the construction site when workers know safety violations are risky, but they cannot stop such behaviours because of production goal (Xu, Zou, & Luo, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation